Patterns of health service utilisation of mothers experiencing mental health problems and intimate partner violence: Ten-year follow-up of an Australian prospective mother and child cohort - Gartland, Deirdre; Hegarty, Kelsey; Papadopoullos, Sandra; Brown, Stephanie (PLOS ONE, 2022)
Objectives Few studies have investigated health service use of mothers experiencing mental health problems or intimate partner violence (IPV). The aim of this study was to investigate health service utilisation of mothers experiencing mental health problems and intimate partner violence ten years after having a first baby. Methods Prospective cohort of 1507 first-time mothers recruited in Melbourne, Australia. Follow-up at ten years incorporated: Center for Epidemiologic Studies Depression Scale, Beck Anxiety Inventory, Posttraumatic Stress Disorder Checklist, Composite Abuse Scale. Results At ten years postpartum, one in four mothers (26.1%) reported depressive, anxiety or posttraumatic stress symptoms, and almost one in five (19.4%) reported recent IPV. Two-fifths of mothers reporting clinically significant mental health symptoms had experienced recent IPV (Odds Ratio = 5.6, 95% CI 3.9–8.1). Less than half of mothers experiencing mental health problems at ten-year follow-up had discussed their mental health with a general practitioner and around one in three had talked to a mental health professional. Two-thirds of mothers experiencing recent IPV had not disclosed this to a general practitioner or mental health professional. Conclusions The findings highlight the extent to which many women deal with IPV and mental health problems without the support that primary health care and mental health care could provide and point to the need for more concerted efforts to strengthen health system responses to these frequently related issues.